Harnessing the Power of Pressurized Separation: Revolutionizing Crude Oil Processing and Storage for Optimal Performance - Nnadikwe Johnson; Samuel Hanotu Kwelle; Nwosi Hezekiah Andrew (Journal Of Data Science, 2025)
The main goal of this research was to simulate a high-pressure (HP) separator to assess how changes in operational factors affect the properties of the products generated. The objective was to improve the efficiency of crude oil processing and storage by analyzing these impacts. The study involved comparing simulation outcomes from two software platforms, namely CHEMCAD and UniSim, to evaluate their effectiveness in modeling and optimizing the separation process.The research outcomes indicated a high level of agreement between the simulated results and actual industrial data, validating their accuracy and reliability. Furthermore, a comprehensive sensitivity analysis was carried out to fine-tune the process parameters, focusing on adjusting key gas stream properties such as temperature, pressure, and flow rate to optimize the separation process effectively. This analysis provided valuable insights into the system dynamics and highlighted areas for potential process enhancement. Notably, the study revealed that increasing the separator inlet pressure from 30 to 80 bar resulted in significant improvements inThe adjustment in separator inlet pressure resulted in a notable reduction in the outlet gas flow rate from 1202 to 871.15 kmol/h, accompanied by an increase in the methane mole fraction from 0.69 to 0.74. Moreover, the rise in pressure led to an escalation in the preheater heating duty from 8.71 to 11.48 GJ/h. Conversely, the simulation findings demonstrated that raising the temperature of the separator feed stream from 43 to 83 ◦C caused a surge in the outlet gas stream flow rate from 871.15 to 1142.98 kmol/h.Furthermore, the variation in temperature led to a decrease in the methane concentration in the gas output and consequently lowered the heating duty required by the heat exchanger. Additionally, the research findings indicated that augmenting the inlet feed flow rate did not yield a substantial effect on the methane gas concentration in the final product.